Direct Patterning of Self Assembled Nano-Structures of Block Copolymers via Electron Beam Lithography - Yoon, Bo Kyung; Hwang, Wonseok; Park, Youn Jung; Hwang, Jiyoung; Park, Cheolmin; Chang, Joonyeon (Macromolecular research, 2005)
This study describes a method where the match of two different length scales, i.e., the patterns from self-assembled block copolymer (<50nm) and electron beam writing (>50nm), allow the nanometer scale pattern mask. The method is based on using block copolymers containing a poly(methyl methacrylate) (PMMA) block, which is subject to be decomposed under an electron beam, as a pattern resist for electron beam lithography. Electron beam on self assembled block copolymer thin film selectively etches PMMA microdomains, giving rise to a polymeric nano pattern mask on which subsequent evaporation of chromium produces the arrays of Cr nanoparticles followed by lifting off the mask. Furthermore, electron beam lithography was performed on the micropatterned block copolymer film fabricated by micro-imprinting, leading to a hierarchical self assembled pattern where a broad range of length scales was effectively assembled, ranging from several tens of nanometers, through submicrons, to a few microns. KCI Citation Count: 11